2009
DOI: 10.1167/9.1.30
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal limits of motion perception across variations in speed, eccentricity, and low vision

Abstract: We evaluated spatial displacement and temporal duration thresholds for discriminating the motion direction of gratings for a broad range of speeds (0.06 degrees/s to 30 degrees/s) in fovea and at +/-30 degrees eccentricity. In general, increased speed yielded lower duration thresholds but higher displacement thresholds. In most conditions, these effects of speed were comparable in fovea and periphery, yielding relatively similar thresholds not correlated with decreased peripheral acuity. The noteworthy excepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
52
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 92 publications
13
52
0
Order By: Relevance
“…These factors influence most aspects of spatial vision-for instance, acuity, peripheral vision, low vision, amblyopia, "tarachopia" (Hess, 1982), and the apparent visual field (Koenderink, van Doorn, & Todd, 2009). Image motions add information about spatial order that partially compensates for neural limitations (Lappin, Tadin, Nyquist, & Corn, 2009). …”
Section: Spatial Uncertainties About Objects Given Their Imagesmentioning
confidence: 99%
“…These factors influence most aspects of spatial vision-for instance, acuity, peripheral vision, low vision, amblyopia, "tarachopia" (Hess, 1982), and the apparent visual field (Koenderink, van Doorn, & Todd, 2009). Image motions add information about spatial order that partially compensates for neural limitations (Lappin, Tadin, Nyquist, & Corn, 2009). …”
Section: Spatial Uncertainties About Objects Given Their Imagesmentioning
confidence: 99%
“…It is well known that the minimum temporal threshold for motion perception is influenced by stimulus speed. Lappin and colleagues [28] examined this phenomenon meticulously, and from their results it is clear that at 3 • /s (the stimulus speed used in the present study) the minimum is ∼40-50 ms. Therefore, we consider it unlikely that the continuous application of flashing stimulation could interfere with our results.…”
Section: Discussionmentioning
confidence: 52%
“…Assuming that the refractoriness caused by a single flash lasts approximately 140 ms [20] and that the period of 12 Hz stimulation is ∼83 ms, the time window not covered by refractoriness is always ∼26 ms, which, in the case of either of the applied stimuli, appears to be too narrow for efficient processing. The minimum temporal threshold for form perception is definitely longer [26], and even if motion is processed more rapidly, thorough and well-documented studies found that the minimum is somewhere near 35 ms [27,28]. It is well known that the minimum temporal threshold for motion perception is influenced by stimulus speed.…”
Section: Discussionmentioning
confidence: 99%
“…McKee and Nakayama (1984) demonstrated similar results and concluded that even in the case of stimulus magnification the threshold value for differential motion detection did not reach the same level in the peripheral visual field as it did in the central visual field. However, there are cases when the opposite can also be observed, e.g., the peripheral visual field is more efficient in detecting movement of stimuli with higher velocities (Finlay, 1982;Lappin et al, 2009). Hence, it seems that there are differences between motion perception in central and peripheral visual fields.…”
Section: Introductionmentioning
confidence: 99%